I will be especially very careful - Child, Lauren; Starkey, Anna.; Tiger Aspect Productions (New York, NY : Dial Books for Young Readers, 2009)
Lola's friend Lotta has a special new coat, and Lola really wants to borrow it.
A Junior Library Guild selection
Accelerated Reader/Renaissance Learning
Keywords: Coats -- Juvenile fiction; Best friends -- Juvenile fiction; Coats -- Fiction; Best friends -- Fiction